2018
DOI: 10.1111/ijfs.13908
|View full text |Cite
|
Sign up to set email alerts
|

Physiochemical and nutritional characteristics, bioaccessibility and sensory acceptance of baked crackers containing broccoli co‐products

Abstract: Summary The effects of the inclusion of broccoli co‐products into crackers on the bioaccessibility as well as their overall physical and nutritional quality were evaluated. Crackers were formulated using a 12.5 or 15.0% flour substitution level. Broccoli‐containing crackers presented higher specific volume and spread ratio and lower weight and specific volume than control crackers (P < 0.05). Crackers containing broccoli co‐products showed an increased green hue and a higher colour intensity (P < 0.05). Incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 28 publications
2
26
0
2
Order By: Relevance
“…In that study, the authors reported that breads containing higher concentrations of broccoli sprouts were unacceptable in terms of aroma, taste, and texture. Similar results were observed by Lafarga, Gallagher et al (), who reported higher overall acceptability scores for crackers containing broccoli co‐products at concentrations ranging between 12% and 15% (w/w) when compared to the controls. Anwar et al (), obtained maximum overall acceptability scores in broccoli‐containing breads at concentrations ranging from 1% to 2% (w/w) and unacceptable textural and sensory properties at higher concentrations.…”
Section: Resultssupporting
confidence: 88%
“…In that study, the authors reported that breads containing higher concentrations of broccoli sprouts were unacceptable in terms of aroma, taste, and texture. Similar results were observed by Lafarga, Gallagher et al (), who reported higher overall acceptability scores for crackers containing broccoli co‐products at concentrations ranging between 12% and 15% (w/w) when compared to the controls. Anwar et al (), obtained maximum overall acceptability scores in broccoli‐containing breads at concentrations ranging from 1% to 2% (w/w) and unacceptable textural and sensory properties at higher concentrations.…”
Section: Resultssupporting
confidence: 88%
“…Improved antioxidant capacity Organoleptic properties unaffected by elaboration [126] Puree and juice made with Broccoli by-products (powder) Epigallocatechin gallate Improved antioxidant anticancer and anti-inflammatory activity by increased Epigallocatechin-gallate in puree Juices is not an optimal carrier of Epigallocatechin-gallate [127] Sponge cake with substitution of white flour (10% and 20%) by White Cabbage byproduct powder Total dietary fiber Increase of dietary fiber Decrease of total quantity of fat and carbohydrates Slight but acceptable decrease of organoleptic properties [128] Microencapsulation of polyphenols extracted from red chicory and red cabbage (nutraceutical) Phenolic compounds Stabilization of pH-dependent light-absorption properties of polyphenols Improvement of the thermal stability of polyphenols, mostly from red cabbage [79] Microencapsulated SFN from broccoli seed extracts (nutraceutical) SFN Powdered complex from Arabic gum and gelatin for encapsulating SFN from broccoli seeds. [129] Microencapsulated of Broccoli ingredient (nutraceutical)…”
Section: Phenolic Compounds Dietary Fiber Glsmentioning
confidence: 99%
“…Recent research into the use of broccoli waste materials undertaken by Lafarga et al . () and Krupa‐Kozak et al . (), showed a distinct lack of consumer acceptance when used in a sponge cake, possibly due to the strong aftertaste.…”
Section: Baked Goods As Functional Foodsmentioning
confidence: 90%